2019
DOI: 10.1002/lsm.23139
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Role of Block Length in Neural Heat Block to Reduce Temperatures During Infrared Neural Inhibition

Abstract: Background and Objectives The objective of this study is to assess the hypothesis that the length of axon heated, defined here as block length (BL), affects the temperature required for thermal inhibition of action potential propagation applied using laser heating. The presence of such a phenomenon has implications for how this technique, called infrared neural inhibition (INI), may be applied in a clinically safe manner since it suggests that temperatures required for therapy may be reduced through the proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 76 publications
(113 reference statements)
1
27
0
Order By: Relevance
“…The inhibition of excitable tissues, 19 21 , 32 36 including both neural and cardiac preparations, by IR light pulses has been studied extensively and is commonly referred to as IR nerve inhibition (INI). The consensus is that the INI results from temperature-dependent changes of passive membrane properties as well as sodium and potassium ion channel kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of excitable tissues, 19 21 , 32 36 including both neural and cardiac preparations, by IR light pulses has been studied extensively and is commonly referred to as IR nerve inhibition (INI). The consensus is that the INI results from temperature-dependent changes of passive membrane properties as well as sodium and potassium ion channel kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…We have explored ways to apply IR inhibition effectively and safely for translational applications. 21 We showed that IR inhibition is safe and reversible in previous acute studies. 4 , 5 In addition to optimizing the IR inhibition protocol (e.g., changing the block length 21 ), we are exploring whether other inhibition modalities could be combined to reduce the IR threshold.…”
Section: Introductionmentioning
confidence: 74%
“…The key advancement allowed by the MANTIS platform is the ability to multiplex optically incompatible imaging techniques such as thermal imaging with nonlinear optical microscopy. Thermal imaging can be used to evaluate fast photothermal processes, such as infrared neural stimulation (48,55,67), with coregistered contrast from nonlinear imaging modalities to study real time biophysical dynamics. To assess the multimodal capabilities of MANTIS, readout of multimodal nonlinear contrast was directly correlated with high-speed temperature changes during infrared neural stimulation in a fresh ex vivo sciatic nerve preparation (Fig.…”
Section: In Vitro Imagingmentioning
confidence: 99%
“…Moreover, optical components that suffice for use between 0.4 and 14 µm wavelengths to encompass visible optical and thermal infrared imaging are not readily available. Finite element heat transfer modeling and Monte Carlo simulations of photon transport in scattering media is often regarded as the benchmark approach for temperature estimation of dynamic photothermal processes in biological samples with high water concentrations (48)(49)(50)(51). Several indirect approaches have been demonstrated including temperature-dependent changes in fluorophore emission, and probe beam deflection microscopy (43,(52)(53)(54).…”
mentioning
confidence: 99%
See 1 more Smart Citation